2021
DOI: 10.3390/jof7090752
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Syntheses of Antiplatelet Metabolites of the Thienopyridines Clopidogrel and Prasugrel Using Fungal Peroxygenases

Abstract: Antithrombotic thienopyridines, such as clopidogrel and prasugrel, are prodrugs that undergo a metabolic two-step bioactivation for their pharmacological efficacy. In the first step, a thiolactone is formed, which is then converted by cytochrome P450-dependent oxidation via sulfenic acids to the active thiol metabolites. These metabolites are the active compounds that inhibit the platelet P2Y12 receptor and thereby prevent atherothrombotic events. Thus far, described biocatalytic and chemical synthesis approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The ability of UPOs to generate pharmacologically relevant substrates is also of particular interest. The conversion of the antiplatelet drug clopidogrel to its active metabolite by different UPOs was also recently demonstrated (Kiebist et al, 2021).…”
Section: Introductionmentioning
confidence: 95%
“…The ability of UPOs to generate pharmacologically relevant substrates is also of particular interest. The conversion of the antiplatelet drug clopidogrel to its active metabolite by different UPOs was also recently demonstrated (Kiebist et al, 2021).…”
Section: Introductionmentioning
confidence: 95%
“…The β-adrenergic blocker propranolol, the non-steroidal anti-inflammatory drug diclofenac, and the antithrombotic prodrug clopidogrel are known to be metabolized by cytochrome P450 monooxygenases in the human body. In previous studies, it was shown that wt Aae UPO is able to perform the same reactions to give the (major) human drug metabolites 5-hydroxypropranolol, 4′-hydroxydiclofenac, and 2-oxoclopidogrel, respectively ( Figure 5 ) [ 15 , 40 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Essential for this type of reaction is the heme cofactor that is coordinated proximally by the thiol of a cysteine residue. Due to their P450-like catalytic mechanism and reaction spectrum, UPOs can be used for the conversion of pharmaceuticals and drugs, e.g., of volixibat ( N -dealkylation) [ 10 ], cyclophosphamide (aliphatic hydroxylation) [ 11 ], propranolol (aromatic hydroxylation) [ 12 ], testosterone (epoxidation) [ 13 ], corticosteroids (side-chain removal by C-C scission) [ 14 ] and clopidogrel (sulfoxidation and epoxidation) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the first steps in the metabolism of thienopyridines 76, clopidogrel 1q, and ticlopidine 1p was oxidation of the thiophene ring by a CYP450 monooxygenase (or UFO peroxygenase) to yield an unstable thiophene epoxide 77. This intermediate isomerized into a 2-hydroxythiophene 78 and its thiolactone tautomers 79a and 79b (Path A, Scheme 15) [159]. Further CYP450-or peroxygenase-catalyzed oxidation of tautomers 78/79a/79b led to a reactive thiolactone S-oxide 80 that hydrolyzed to a sulfenic acid 81 and was trapped using dimedone [120,[160][161][162][163][164].…”
Section: Monooxygenase-catalyzed Thiophene Ring Oxidation Of Thienopyridine Prodrugsmentioning
confidence: 99%
“…The unstable S-oxide 84 was trapped by dienophiles, e.g., N-methyl-(NMM) and N-ethyl-maleimide (NEM) [119,120] to give product 86, or thiols, e.g., glutathione (GSH) to give adducts 87 [173]. The oxidation reactions (Path A and Path B) were also catalyzed by unspecific fungal peroxygenases (UFO) in the presence of ascorbic acid and hydrogen peroxide [159].…”
Section: Monooxygenase-catalyzed Thiophene Ring Oxidation Of Thienopyridine Prodrugsmentioning
confidence: 99%